Trigger tools na vigilância de reações adversas a medicamentos em pacientes críticos com COVID-19 - Cavalcante, Viviane Nascimento (2024)
Adverse drug reactions (ADRs) are adverse events resulting from undesirable effects when used in normal doses. These reactions may occur during treatment in intensive care units (ICU) or result in the need for intensive care. Furthermore, they are among the main causes of death in hospitalized patients. The objective of the study is to analyze the feasibility of using trigger tools to identify ADRs in critically ill patients with COVID-19. This is a study carried out in two phases. The first consisted of a systematic literature review to identify the triggers used in the literature to detect ADRs in intensive care patients. In the second stage, a retrospective, descriptive and analytical observational study was carried out using trigger tools, conducted with critically ill patients with COVID-19. The review included four primary studies, which suggest that an ideal trigger model is one that includes more efficient alerts to identify a greater number of possible harms to the patient. This model consists of the prescription or abrupt suspension of certain medications, changes in laboratory tests and specific events during the period of hospitalization, subject to modifications to adapt to the practice or culture of the institutions. In the observational study, 1068 triggers were identified in 212 medical records of patients with COVID-19, of which 144 (13.5%) were related to ADRs. The most frequent events were disorders of the hematological and lymphatic system (31.0%, n=44), metabolic and nutritional disorders (29.0%, n=42), hepatobiliary disorders (18.0%, n=12), gastrointestinal (7.0%, n=10) and cardiac (7.0%, n=10). Furthermore, of the total ADRs detected, 17.4% (n=25) involved drug interactions and 71.5% (n=103) were related to the use of potentially dangerous medications (PPM). Of the twenty-four triggers used, ten showed a good performance to predict ADR: “flumazenil”, “lethargy”, “QT interval prolongation” “platelets < 50,000 mm3”, “serum or capillary glucose <50 mg/dl”, “vitamin K”, “calcium polystyrenesulfonate or polarizing solution (hypertonic glucose + insulin)”, “excessive sedation”, “rash” and “abrupt suspension of medication”. Trigger tools were characterized as an effective method for detecting ADRs in the ICU and were also useful for detecting these events in critically ill patients with COVID-19. This allowed us to know the profile of ADRs that occurred, providing information that can contribute to designing strategies to improve quality in intensive care.